Reinhardtia elegans Mart. (Arecaceae): an endemic palm from the Mexican cloud forest - Ibarra-Manríquez, Guillermo; Mendoza, Ana (Instituto de Ecología, A.C., 2003)
Reinhardtia elegans Mart. (Arecaceae) is a Mexican endemic species occurring in some cloud forests of Oaxaca and Chiapas, whose importance  has been poorly documented in floristic studies of southeastern Mexico. We provide information about its habitat and population structure in La Chinantla region in Oaxaca, Mexico.